An Experiment on Precognition with Planarian Worms - Alvarez Gonzalez, Fernando (Journal of Scientific Exploration, 2016)
The ability for precognition of a noxious stimulus (a startle sound ) was explored in a simple aquatic animal, the black planarian worm Dugesia dorotocephala. During the experimental trials, planarians were put individually in a testing chamber and after 3 minutes either an audio startle stimuli or a control moments of silence was randomly presented. Subjects were filmed and the frequency of their Head Movements (this behavior being indicative of distress and/or ambient exploration) was registered in the 10 seconds segments immediately and one minute before presentation for the experimental subjects and immediately before and one minute before the time point 3 min from start for the controls. Nonparametric comparison of the frequencies of Head Movements for the experimental and control worms showed that the former reacted to the startle stimuli before presentation immediately and one minute before stimulation and the control subjects did not react